The story of Johnny Appleseed - Aliki (New York : Aladdin Paperbacks, 1963)
Retells the wandering of John Chapman whose devotion to planting apple trees made him a legendary figure in American history.
Ages 4-8.
Keywords: Appleseed, Johnny, -- 1774-1845 -- Juvenile literature; Apple growers -- United States -- Biography -- Juvenile literature; Frontier and pioneer life -- Middle West -- Juvenile literature